The Prevalence and Predictors of Tuberculin Positivity in Subjects Screened for Reasons other than Contact Investigation - Eduardo Hernández-Garduño; R Kevin Elwood (Canadian Respiratory Journal)
BACKGROUND: No previous studies have estimated the rates of tuberculin positivity (TP) in noncontact populations within the same community, which is important for prioritizing and implementing preventive measures.